Becoming A Cosmopolitan Patriot: A Perpetual Imagining of Israel Education. Issue 1 (2nd January 2023) - Ariel, Jonny
ABSTRACT: When Israel, Jewish identity and education are each in a state of profound flux, Israel education for Jews will necessarily be dynamic. In response, an orienting prism is proposed which seeks that Jews inquire appreciatively into Israel with diverse Israelis, whilst using historical thinking. The aim is that there emerge numerous ethical paths to realize patriotic dreams to participate actively in the cosmopolitan world, thus enabling Jewish flourishing.